(untitled) (Journal of Hama University, 2021)
This study aimed to evaluate the histological reaction of the Metal Trioxide Aggregate (MTA) and make comparison with Platelet Rich Fibrin (PRF) as a dental pulp capping materials in rabbit teeth and studying the inflammatory response and the formation of the dentin bridge. Ten male New Zealand rabbits were divided into two main groups (5 rabbits in each group) according to the study and observation periods (3 days, and 3 weeks ). The four upper and lower incisors for each rabbit were included in the study, so each major group consist of 20 rabbit teeth, and MTA was randomly applied to 10 teeth (5 upper incisors, 5 lower incisors), and PRF was randomly applied to 10 teeth (5 upper incisors, 5 lower incisors) in each group. A class V cavity was made and prepared on the vestibular (bucal) surface of the incisors, and mechanical exposure to the pulp was performed, and the tested materials were applied after achieving hemostasis in the pulp, then the teeth were restored with GIC . Experimental animals were sacrificed after the end of observation period, and incisors were extracted and placed in formalin 10%, after that pathological tissue sections on glass slide were prepared and stained and then examined microscopically. The results of this study revealed that there are no statistically significant differences at the 95% confidence level in the inflammatory response and the formation of the dentin bridge between the MTA and the PRF in all groups. In MTA second observation group ( ended at 3ed week), the result showed lower degree (severity) of inflammation and thicker dentin formed bridge in comparison to MTA first observation group ( ended at 3ed day), and in PRF second observation group ( ended at 3ed week), the result showed lower degree (severity) of inflammation and thicker dentin formed bridge in comparison to PRF first observation group ( ended at 3ed day). We conclude the similarity of the histological reaction and inflammation responses of PRF with MTA as pulp capping materials.